(untitled) (Huellas, 2019)
The growth of enclosed urban developments in the city of Mar del Plata is addressed on the basis of the precepts of a cultural approach in Geography. This constitutes a phenomenon where urban developers offer all kinds of amenities. The infrastructure available to these enterprises, the morphology they present and the social representations they generate has led to a categorical transformation in the local territory. This change is linked to the processes of socio-territorial fragmentation that take place in the large metropolitan areas of the region and the country. The methodology applied is the case study of the new enclosed urbanizations in the city of Mar del Plata. For the purposes of this work, methods of bibliographic compilation, statistical studies, semi-structured surveys, interviews with key social actors and field research have been used. This article tries to contribute to the study of the spatial dimension of resignification practices and the importance of places. In this case, the link between commercial strategies and advertising guidelines, which are used by the media, for the construction and growth of enclosed urbanizations in the city of Mar del Plata.